Understanding Differentiation of User Roles and Gamification in a Professional Online Community: A Case Study - Imroz, Sohel M. (Journal of Management Policy and Practice, 2021)
Online communities can flourish only when users participate by contributing meaningful content. A clear understanding of the gamification concept and user roles are crucial in creating a successful online community. This case study examined user roles and gamification in Now Community® —a popular online community for ServiceNow professionals. Ten user roles and five gamifications components were identified. While simply gamifying an online community does not guarantee increased user participation and engagement, learning how user roles and gamification work in a successful and popular professional online community can be beneficial. Results of this study should provide valuable insights and help other professionals and practitioners who wish to gamify their online communities.